Zero Waste-Based Organic and Non-Organic Waste Sorting Education - Prodyanatasari, Arshy; Diasandy, Deva Raka Satria; Azizah, Laila Nur; Izati, Lufia Elen Ayu; Hidayat, Abdullah Farikh (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
Waste is generated from the activities of living organisms and is divided into organic, inorganic, and hazardous categories. Proper disposal of waste is crucial for minimizing environmental pollution. One effective approach is educating people about Zero Waste principles and implementing the 3Rs: reduce, reuse, and recycle. This activity involved repurposing mineral water gallons as bins for organic and inorganic waste. The PkM activity took place at SD YBPK Kota Kediri on April 26, 2024, targeting all students from grades I to VI, totaling 70 participants. The PkM was conducted using the Participatory Action Research (PAR) method and work performance evaluations. The outcomes of this PkM activity included increased knowledge among participants about identifying organic and inorganic waste, as well as heightened awareness of proper waste disposal according to waste classification.